Honduras : Enhanced Initiative for Heavily Indebted Poor Countries Completion Point Document. (IMF Staff Country Reports; Country Report, 2005)
The paper discusses the consideration of Honduras's Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). The interim relief provided under the enhanced HIPC Initiative has allowed the government to increase social spending. Controlling the public sector wage bill and maintaining strong revenue collection is critical for sustaining a stable macroeconomic framework and adequate poverty reduction efforts. Efforts are also needed to reduce vulnerabilities and improve the resilience to external shocks by introducing more flexibility into the exchange rate regime.